2021
DOI: 10.1021/acsanm.1c01810
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Azo Dyes in Sunlight Promoted by Nitrogen–Sulfur–Phosphorus Codoped Carbon Dots

Abstract: Removal of organic contaminants such as azo dyes is highly desirable because of their toxicity, stability, and mutagenic properties. Herein an efficient method for the photodegradation of two well-known model azo dyes, namely metanil yellow (MY) and methyl orange (MO), under sunlight by multiple-heteroatomdoped carbon dots (CD) (nitrogen-, sulfur-, and phosphorusdoped-CD (NSP-CD)) is presented. The photodegradation results favored sunlight as a sustainable light source, as its value of t 1/2 is significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 69 publications
0
46
0
Order By: Relevance
“…94 Also, NSP-CD were prepared using PEG, H 3 PO 4 , and Lcysteine as C, P, and N/S sources and photocatalytic activities toward the degradation of MO and methanine yellow (MY) dyes were analyzed. 95 Li et al prepared NSP-tri doped CD via the hydrothermal method using H 3 PO 4 and sulfonamide with a QY of ∼33%. A UV absorption spectra of NSP-CD is shown in Figure 5f, and the inset is the images of NSP-CD solution under daylight and UV-light showing fluorescence.…”
Section: Synthesis Of CD Doped-cd and Cd-basedmentioning
confidence: 99%
See 4 more Smart Citations
“…94 Also, NSP-CD were prepared using PEG, H 3 PO 4 , and Lcysteine as C, P, and N/S sources and photocatalytic activities toward the degradation of MO and methanine yellow (MY) dyes were analyzed. 95 Li et al prepared NSP-tri doped CD via the hydrothermal method using H 3 PO 4 and sulfonamide with a QY of ∼33%. A UV absorption spectra of NSP-CD is shown in Figure 5f, and the inset is the images of NSP-CD solution under daylight and UV-light showing fluorescence.…”
Section: Synthesis Of CD Doped-cd and Cd-basedmentioning
confidence: 99%
“…Recently, multiple-heteroatom doped CD (NSP-CD) was used to degrade azo dyes (MO and MY) in acidic medium. 95 A light-assisted comparative study was also performed in the presence of a 100 W bulb light and under sunlight. The obtained result showed that NSP-CD has great photodegradation ability under sunlight in comparison to bulb light, and as the rate increases (K sunlight > K bulb-light ), the half-life t 1/2 decreases (∼10 times) as shown in Figure 9c,d The photogenerated e − in the CB of SnS 2 can easily be inserted into the CD with the destruction of charge recombination followed by an improved photocatalytic activity.…”
Section: Photocatalytic Applicationsmentioning
confidence: 99%
See 3 more Smart Citations